Cretocrenis burmanicus, the first Mesozoic amber inclusion of a water scavenger beetle (Coleoptera: Hydrophilidae). (September 2017) - Fikáček, Martin; Minoshima, Yûsuke N.; Komarek, Albrecht; Short, Andrew E.Z.; Huang, Diying; Cai, Chenyang
Abstract: Cretocrenis burmanicus, gen. et sp. nov. is described from Burmese amber and represents the oldest known amber inclusion of the family Hydrophilidae (Coleoptera: Polyphaga). The new genus resembles the small-bodied modern genera of the tribe Anacaenini and the subfamily Acidocerinae, and the morphology of the venter and male genitalia suggest that it belongs to the Horelophus+Crenitis clade of the tribe Anacaenini. The fossil is described in detail, illustrated, and compared with extant hydrophilid genera.